Trunk muscle activity in healthy subjects during bridging stabilization exercises - Stevens, Veerle K; Bouche, Katie G; Mahieu, Nele N; Coorevits, Pascal L; Vanderstraeten, Guy G; Danneels, Lieven A (BMC musculoskeletal disorders, 2006)
Trunk bridging exercises are often used as therapeutic exercises for lumbopelvic stabilization. These exercises focus on the retraining of muscle coordination patterns in which optimal ratios between local segmental stabilizing and global torque producing muscle activity are assumed to be essential. However, a description of such ratios is lacking. The purpose of this study was to investigate both relative (as a percentage of maximal voluntary isometric contraction) muscle activity levels and ratios of local to global muscle activity, during bridging stabilization exercises. Thirty healthy university students (15 men, 15 women) with a mean age of 19.6 year volunteered to perform 3 bridging exercises (single bridging, ball bridge and unilateral bridging). The surface electromyographic activity of different trunk muscles was evaluated on both sides. During all bridging exercises, the ratio of the internal oblique to the rectus abdominis was very high due to minimal relative activity of the rectus abdominis. In general, the ratio of the internal/external abdominal oblique activity was about 1. However, during the unilateral bridging exercise, the ipsilateral internal/external abdominal oblique activity ratio was 2.79 as a consequence of the significant higher relative activity of the internal oblique compared to the external oblique. The relative muscle activity and the ratios of the back muscles demonstrated similar activity levels for all back muscles, resulting in ratios about 1. Both the minimal relative activity of the rectus abdominis and the high internal oblique to the rectus abdominis activity ratio reported in the present study are in accordance with results of other trunk stabilization exercises. The relative muscle activity and the ratio of the abdominal obliques seem to alter depending on the task and the presumable need for stability. The findings concerning the relative muscle activity and the ratios of the back muscles support the assumption that during these bridging exercises, all back muscles contribute in a similar way to control spine positions and movements in a healthy population.